"Hey! Mr Prime Minister!": The Simpsons Against the Liberals, Anti-fandom and the "Politics of Against". (July 2022) - Barnes, Renee; Middlemost, Renée
Memes and popular culture have become central to our understanding of contemporary politics. Recent fan scholarship has shown how popular culture encourages audiences into discussion, participation, creativity, intervention, and evaluation in politics. In this article, we build on existing scholarship analysing political meme creation and distribution, which to date has primarily focused primarily on American politics. Using a case study of the Facebook group The Simpsons Against the Liberals (the conservative ruling party in Australia), we examine how the anti-fannish behaviors of appropriating and remixing content, affective investment, and community collective identity formation is activated through othering or a "politics of against" (Sandvoss, 2019). The Simpsons Against the Liberals page features memes which insert current Australian political issues, scandals, and controversies into the fictional world of The Simpsons . As we argue, the community is bound by its anti-fandom of the Australian Liberal party, rather than a specific unifying feature. While anti-fandom is driven from hate and dislike, this case study demonstrates that a form of anti-fandom exists in which pleasure is derived from the use of humor to perform acts of citizenship and imagined community. Specifically, this article will examine the flurry of creative production during the 2019/20 Australian bushfire crisis—centered around the controversial behavior of Prime Minister Scott Morrison—as a form of contemporary civic action and activism rooted in anti-fan practices.